Challenges in Implementing The "Freedom to Learn, Campus Freedom" Curriculum To Shape Citizens With Religious and Nationalistic Characters - Irayanti, Irma; Wulandari, Wulandari; Winata, Edrian; Subaida, Sitti (Civic Education Perspective Journal, 2025)
The implementation of the "Merdeka Belajar, Kampus Merdeka" (MBKM) or “Curriculum Freedom to Learn, Campus Freedom” curriculum in higher education poses challenges in integrating religious and national values, ensuring inclusivity, and adapting to societal changes. This study explores the impact of the MBKM curriculum on shaping citizens with religious and nationalistic characters in Indonesia's higher education system. Utilizing a qualitative research method with a literature review design, the study considers criteria such as relevance, recent publication dates, and diverse perspectives in literature selection. Thematic analysis is employed for data analysis, addressing potential biases through reflexivity and peer debriefing. Findings emphasize the need for continuous curriculum review to align with societal values and regulations. While the focus on Indonesia's higher education system may limit generalizability, discussing variations in cultural and educational contexts would enhance applicability. Ethical and legal considerations in integrating religious and nationalist values are crucial, requiring a thorough discussion to ensure alignment with pluralism and individual rights.